COMPOSITIONS OF TITANOMAGNETITE IN BASALT OF THE CAPE VERDE FRACTURE ZONE - Kaleda K.G. (My University, 1989)
Transform-fault zones are among the three types of plate boundaries recognized in new global tectonics. Although the volcanic activity in these zones undoubtedly occurs on a smaller scale than on the two other types of plate boundaries, it has attracted a great deal of attention, mainly because transform faults represent in many cases the boundaries between igneous provinces with chemically and isotopically differing rocks. Also, the very presence of faults affects the chemistry of the vicinal rocks. The authors investigated the compositions of magnetic minerals in basalt from the Cape Verde Fracture Zone, dredged during the 3rd and 6th cruises of the R/V Akademik N. Strakhov. Petromagnetic investigations showed that the ferrimagnetic components of the basalt is represented by practically unaltered or slightly oxidized titanomagnetite. The average Curie-point temperatures, which reflect the compositions of the magnetic minerals, are clearly lower in basalt from the transform-fault valley. The differences in the Curie points, and in compositions of titanomagnetites from basalts of the Cape Verde Fracture Zone suggest that the pressure in the chamber under a transform fault is 2 to 5 kbar higher than under the ridge. A difference of 3 percent in the content of TiO2 in titanomagnetite results in a difference in Curie temperatures of 70 to 80°C which, at the temperature gradients existing near the ridges, could affect the thickness of the magnetoactive layer.